(untitled) (Journal of Informatics Education and Research, 2025)
Besides the consistent focus of the Reserve Bank of India, Central Vigilance Commission, and organisations themselves towards preventive vigilance, the number of fraud cases and instances of wrongdoings by employees is not going down. Therefore, there is a need to work on the molecular units, which are generated by factors that intermediate between employees and their behaviours, in addition to preventive vigilance initiatives for products and processes. This study aims to examine various system, individual, psycho-social, and socio-cultural related factors. Responses of punished employees, employees that are already facing inquiry, their Controllers, Disciplinary Authorities, and Inquiry Authorities using structured questionnaires finalised after consulting experts from Public Sector Banks were collected from 3800 respondents. The study revealed that PSBs need to strategise on these factors, such as training employees on behavioural, subject knowledge, policies and guidelines, etc., filling up the gaps/weaknesses in systems and third-party service providers to arrest instances of wrongdoings, improving the ethical environment of PSBs, and build a better organisation.